A SHIFTING STANDARDS PERSPECTIVE OF MASCULINITY IN AVOSKIN YOURSKINBAE SHIELD OF SUN ADVERTISEMENT - Alifah Adjani Prasetyo; Almeida Prastiwi; Ayutia Kusumastuti; Muhammad Fadhilah Putra; Muizzu Nurhadi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Advertisements nowadays have become increasingly gender-neutral in recent years rather than targeting a single gender. The Calvin Klein perfume in 1994 was the first time the product was targeted at both a guy and a lady in the tagline. As well as cosmetics and skin products that are transitioning toward more gender-neutral items in unisex packages, there is also starting to be a shift in transgender people to their market and public advertising. It helps to improve cosmetics manufacturing and encourages certain people to express themselves regardless of gender. It also influences how masculinity and femininity change from the stereotype. In this case, we will use the Avoskin YourSkinBae Shield of Sun advertisement that shows the shifting of masculinity using John Fiske’s semiotic analysis of television code, which has three levels: reality, representation, and ideology. The result shows how the Avoskin YourSkinBae Shield of Sun advertisement wants to represent the new forms of masculinity that appear in the realm of popular representation.